Gene transfer to the vascular system: novel translational perspectives for vascular diseases - Remes, Anca; Basha, D. I.; Frey, N.; Wagner, Andreas H.; Müller, Oliver J. (Biochemical pharmacology, 2020)
Although vessels are directly exposed to the bloodstream, vascular gene transfer is rarely used as a tool for preclinical studies for several reasons: (i) viral and non-viral vectors show a low transduction efficiency in the vascular system; (ii) classical vascular gene therapy approaches such as treatment of peripheral or cardiac ischemia are focusing on non-vascular target cells; and (iii) vascular diseases are rarely monogenetic, thus gene replacement approaches are uncommon. Here, we provide an overview of recent approaches in developing novel vectors and modes of application for improved transduction efficiency of large and small vessels. Increased availability of such tools for vascular gene transfer has already facilitated preclinical studies addressing a broad variety of vascular diseases like transplant vasculopathy, atherosclerosis, and hereditary aortic diseases such as Marfan syndrome.